Poster Presentations 2019
DOI: 10.1136/annrheumdis-2019-eular.1094
|View full text |Cite
|
Sign up to set email alerts
|

Fri0128 a Novel Formulation of Ct-P13 (Infliximab Biosimilar) for Subcutaneous Administration: 1-Year Results From a Part 1 of Phase I/Iii Randomized Controlled Trial in Patients With Active Rheumatoid Arthritis

Abstract: BackgroundEfficacy and safety of a new subcutaneous (SC) formulation (CT-P13 SC) up to Week 30 were comparable with intravenous (IV) formulation (CT-P13 IV) in both patients with rheumatoid arthritis (RA) [1] and Crohn's disease [2].ObjectivesThis report is to further investigate pharmacokinetics, efficacy and overall safety of CT-P13 SC in patients with RA throughout the 1-year treatment period.MethodsPatients with active RA (presence of 6 or more swollen and tender joints [of 28 assessed], and serum C-reacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 0 publications
2
13
0
Order By: Relevance
“… 22 Efficacy up to Week 54 was similar between treatment arms in terms of mean DAS28 (CRP) scores, even after the CT-P13 IV group switched to CT-P13 SC at Week 30. 22 In terms of PK, mean serum concentrations consistently exceeded the threshold target–therapeutic concentration in Part 1 19 and Part 2. 22 Drug exposure was well maintained, with trough serum concentrations higher and more constant with CT-P13 SC versus CT-P13 IV: 19 , 22 this high consistency in drug exposure could enhance treatment options for patients.…”
Section: Innovative Biologic Development: Ct-p13 Sc Case Studymentioning
confidence: 97%
See 3 more Smart Citations
“… 22 Efficacy up to Week 54 was similar between treatment arms in terms of mean DAS28 (CRP) scores, even after the CT-P13 IV group switched to CT-P13 SC at Week 30. 22 In terms of PK, mean serum concentrations consistently exceeded the threshold target–therapeutic concentration in Part 1 19 and Part 2. 22 Drug exposure was well maintained, with trough serum concentrations higher and more constant with CT-P13 SC versus CT-P13 IV: 19 , 22 this high consistency in drug exposure could enhance treatment options for patients.…”
Section: Innovative Biologic Development: Ct-p13 Sc Case Studymentioning
confidence: 97%
“… 22 In terms of PK, mean serum concentrations consistently exceeded the threshold target–therapeutic concentration in Part 1 19 and Part 2. 22 Drug exposure was well maintained, with trough serum concentrations higher and more constant with CT-P13 SC versus CT-P13 IV: 19 , 22 this high consistency in drug exposure could enhance treatment options for patients. 19 In addition, overall safety profiles were comparable between arms for both study parts.…”
Section: Innovative Biologic Development: Ct-p13 Sc Case Studymentioning
confidence: 97%
See 2 more Smart Citations
“…They also discussed the results collected from clinical trials phase I/III studies from June 2018 to August 2018 in their entirity. 43 Celltrion, a South Korean biotechnology company, conducted the research of one year and reported the pharmacokinetics, efficacy and overall safety data of subcutaneous form of CT-P13 in rheumatoid arthritis. 44 Financial gains with the implementation of a biosimilar concept were noticed from the economic budget standpoint and have drawn the attention of economists.…”
Section: Infliximab Biosimilar (Ct-p13) As a Potential Substitute Formentioning
confidence: 99%